Analysis of the power-to-heat potential in the European energy system. (April 2018) - Yilmaz, Hasan Ümitcan; Keles, Dogan; Chiodi, Alessandro; Hartel, Rupert; Mikulić, Martina
Abstract: The European power system is currently experiencing new challenges due to growing shares of intermittent renewable energy sources. Compared to other flexibility options, power-to-heat (PtH) technologies have a high level of maturity. The goal is, therefore, to analyse the potential for PtH in the European energy system and possible business models that enable the exploitation of these potentials. A literature review on the European and country-level potential for PtH is carried out revealing a wide range of these potentials. An own approach assesses the potential in district heating for selected European countries. PtH potential makes up a remarkable share of the peak electrical load, but varies due to the inhomogeneous nature of the investigated national energy systems and different weather conditions. Highlights: Compared to other flexibility options PtH devices have a high level of maturity. Providing control reserve power is for large-scale PtH an applied business model. Marketing on spot market is currently for PtH applications not feasible. A wide range of PtH potentials across European member states in literature. PtH potential due to excess electricity in district heating about 20 GW in 2030.